Determinants of poverty and income inequality on the islands of Sumatra and Java - Candra Mustika; Rahma Nurjanah; Sylvia Kartika Wulan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Poverty and inequality are the main problems faced by a country including Indonesia. The purpose of this study was to determine and analyze the comparison of poverty and inequality levels on the islands of Sumatra and Java and to analyze the effect of the human development index (HDI), gross regional domestic product (GRDP), the level of open unemployment (TPT) and total population on poverty and income distribution inequality in Sumatra and Java. The research method used is quantitative descriptive with multiple regression analysis using panel data with provincial research objects on the islands of Sumatra and Java. Based on the results of the study, if you look at the comparison of the poverty rate on the island of Sumatra and Java, based on the data, it can be seen that the average poverty rate on the island of Sumatra is 10.6%, which is higher than the average poverty rate on the island of Java, which is 8.8%. while the level of inequality in income distribution on average in Sumatra is 0.327, lower than the average income distribution inequality in Java, which is 0.393. The regression results show that on the island of Sumatra the HDI variable has a significant negative effect on poverty and inequality, GRDP has a significant negative effect on poverty and poverty has a positive effect on inequality. TPT has a significant positive effect on poverty and not significant on inequality. Total population is not significant to poverty and inequality. While the regression results on the island of Java show that the HDI variable has a significant negative effect on poverty and not significant on inequality. GRDP has no significant effect on poverty and inequality. TPT has a significant positive effect on poverty and not significant on inequality. And population has no significant effect on poverty and inequality.